STRATEGI PENGEMBANGAN USAHA BUDIDAYA IKAN KERAPU SISTEM KERAMBA JARING APUNG DI TELUK AMBON DALAM - Irawati Irawati; Muhidin Syamsuddin (Universitas Batangahari Jambi, 2020)
The development of grouper aquaculture production in the waters of Teluk Ambon Dalam (TAD) has increased from year to year, both in the amount of production, aquaculture household and the area of cultivation land. This indicates that the community is increasingly reading the opportunities for grouper farming in Ambon Dalam Bay. Increased production of course must be followed by certainty of market availability, because the success or failure of a cultivation business is determined by market conditions. On this basis, the research entitled